If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 = 3x + 12 Reorder the terms: 18 + 2x = 3x + 12 Reorder the terms: 18 + 2x = 12 + 3x Solving 18 + 2x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 18 + 2x + -3x = 12 + 3x + -3x Combine like terms: 2x + -3x = -1x 18 + -1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 18 + -1x = 12 + 0 18 + -1x = 12 Add '-18' to each side of the equation. 18 + -18 + -1x = 12 + -18 Combine like terms: 18 + -18 = 0 0 + -1x = 12 + -18 -1x = 12 + -18 Combine like terms: 12 + -18 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 4x+3x-3=20 | | 5d-12=23 | | 0.1=3x+78 | | 15+4c=27 | | 6(g-2)+g=6(g-4) | | 5c-7=41 | | 8-8x-4=-17+4x-15 | | (4x+1)=(5x-15) | | 9m+11=38 | | -3=x/5+5 | | 2x-10=-3(x-5) | | .21428571a+.95238095=.57142857 | | 7-(3y-9)=1-4y | | 3x+15=3+5x-8 | | -1x-3=x+4 | | -3x-12=9x+12 | | 28=2d | | -5x+30-7x=3x+120 | | 4x^2-39x+81= | | 3x-2y=33 | | 2x+5x+10=-60 | | 8r^2-10r+3=0 | | 4p*5q=60y | | x*0.10+0.35=10 | | -2K+10=-12 | | 6x-4=-3x+5 | | 13y-3=53-y | | 4p+5q=60y | | a/6=-9 | | 5x^2-24x=-28 | | 7x+14=9x+2 | | x^2-12xy+20y^2= |